Perancangan Stand Ronde Bondowoso Nyonya Tjandrawati di Plaza Surabaya - Maria Veronica Ariella Siswanto; Stephanus P Honggowidjaja; Grace Setiati Kattu (Intra, 2018)
The growing human need on food causes Indonesian culinary to be in a strategic position for fast food supply. Thus, Ronde Bondowoso Nyonya Tjandrawati is improving its product quality so Ronde will be widely known among society. Aside from its quality, Ronde Bondowoso Nyonya Tjandrawati also has to pay more attention to its stand design, since the current stand does not reflect its vision & mission yet and answer its sales activity. The products sold are not well organized hence lack of interest from consumers to simply visit/stop by at the stand. Therefore, Ronde Bondowoso Nyonya Tjandrawati’s stand design is expected to solve these problems so that it can be widely known among society.